PENGARUH BRAND KNOWLEDGE TERHADAP BRAND PREFERENCE CALON MAHASISWA PASCASARJANA: BUKTI EMPIRIS PADA PROGRAM MAGISTER MANAJEMEM UNPAR - Ronald Chandra Fattama (Jurnal Riset Manajemen dan Bisnis, 2014)
One of nicknames that given to Bandung is city of students. It called that way, because of many institutions both public and private in Bandung. Some study estimates that higher education’s demand will increase about four times in 2025. Students that sign up to Parahyangan Catholic University Master of Management had a declining tendency. That delcining tendency is allegeldy because marketing program and promotion that used by Parahyangan Catholic University didn’t go well. The purpose of this research is generally to determine the effect of Parahyangan Catholic University’s brand knowledge on prospective student’s brand preference.The analysis of this research using multiple regression to determine the effect of Parahyangan Catholic University Master Management’s brand awareness and iamge on prosprective student’s brand preference. The findings of this result show that Parahyangan Catholic University Master of Management is recommended to enhance their marketing program and promotion. Marketing program and promotion need to be increase in order to enhance prospective student’s brand awareness and brand image, which leads to increase number of student that sign up for Master Managemen itself. Keywords: brand knowledge, brand image, brand preference, higher education